Evaluation of the osteogenic differentiation of gingiva-derived stem cells grown on culture plates or in stem cell spheroids: Comparison of two- and three-dimensional cultures - Lee, Sung-Il (Exp Ther Med, 2017)
Three-dimensional cell culture systems provide a convenient in vitro model for the study of complex cell-cell and cell-matrix interactions in the absence of exogenous substrates. The current study aimed to evaluate the osteogenic differentiation potential of gingiva-derived stem cells cultured in two-dimensional or three-dimensional systems. To the best of our knowledge, the present study is the first to compare the growth of gingiva-derived stem cells in monolayer culture to a three-dimensional culture system with microwells. For three-dimensional culture, gingiva-derived stem cells were isolated and seeded into polydimethylsiloxane-based concave micromolds. Alkaline phosphatase activity and alizarin red S staining assays were then performed to evaluate osteogenesis and the degree of mineralization, respectively. Stem cell spheroids had a significantly increased level of alkaline phosphatase activity and mineralization compared with cells from the two-dimensional culture. In addition, an increase in mineralized deposits was observed with an increase in the loading cell number. The results of present study indicate that gingiva-derived stem cell spheroids exhibit an increased osteogenic potential compared with stem cells from two-dimensional culture. This highlights the potential of three-dimensional culture systems using gingiva-derived stem cells for regenerative medicine applications requiring stem cells with osteogenic potential.